Kompensasi Dan Kinerja Pegawai : Peran Mediasi Dari Kepuasan Kerja: Studi Pada Badan Pendidikan Dan Pelatihan Provinsi Jawa Timur - Moehammad Budi Widajanto; Setiyawan Sukin Adiyanto (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
One of the goals of an organization depends on the good or bad performance of its employees. Therefore, an organization or institution must be able to pay attention to its employees, direct, and motivate them to improve employee performance. Employees who have good performance will be able to carry out work according to the tasks assigned to them, understand the relationship between their work and the tasks of others, understand the institution's targets, and be able to understand and resolve obstacles faced in carrying out their duties. This study aims to examine the influence of compensation on employee performance; examine whether compensation has an effect on employee job satisfaction; examine job satisfaction as a moderating influence between compensation and employee performance. The population in this study were all permanent employees of the East Java Provincial Education and Training Agency, totaling 161 people. Based on calculations using the Slovin formula, a sample of 115 people was taken. The analysis technique used moderated regression analysis. Based on the results of the analysis, it was proven that compensation had an effect on employee job satisfaction at the East Java Provincial Education and Training Agency. Job satisfaction moderates the influence between compensation and employee performance at the East Java Provincial Education and Training Agency.